Cost Effective Surface Disruption Detection System for Paved and Unpaved Roads - Mumbere Muyisa Forrest; Zhigang Chen; Shahzad Hassan; Ian Osolo Raymond; Karim Alinani (IEEE Access, 2018)
Roads are exposed to road surface disruptions (RSD) because of erosion, poor water drainage, rain, and soil quality. A delay in maintenance results in severe road damage that blocks the traffic for several days. Up to now, RSD detection on unpaved roads is done manually or reported by drivers. Conversely, different techniques have already been proposed for paved roads, such as vibration, image, and laser scanning. Unfortunately, the methods proposed for paved roads are not directly applicable for unpaved roads due to constraints and properties of RSD and pothole on unpaved roads. Therefore, this paper proposes a novel and low-cost method of detecting RSD based on ultrasonic sensors. The suggested model uses, as input data, relative distances collected by ultrasonic sensor beams, compute the approximate potholes and bumps on surfaces and outputs 2-D surface state map. This innovative and applicable approach has been tested on unpaved and paved roads and showed an accuracy of 94% regarding pothole characteristics (size, surface, and depth) on both paved and unpaved roads. A pothole detection rate of 62% was achieved on the paved road. Furthermore, the implemented algorithm is adaptable through a number of thresholds along with the desirable surface-sensor distance, the required RSD, the sensor’s velocity, and the distance between measurements. The results showed that the system could detect RSD and give valuable information which can help the maintenance team to plan for repair.